2021
DOI: 10.3390/medicina57010061
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Athletes in Italy during 2019: Internet-Based Epidemiological Research

Abstract: Background and objectives: An Italian nationwide pre-participation screening approach for prevention of sudden cardiac death in athletes (SCD-A) in competitive sportspeople showed promising results but did not achieve international consensus, due to cost-effectiveness and the shortfall of a monitoring plan. From this perspective, we tried to provide an epidemiological update of SCD-A in Italy through a year-long internet-based search. Materials and Methods: One year-long Google search was performed using manda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…In the present study, football-related age-specific mortality was found to be 0.41 per 100,000 population and proportional mortality was 0.30 per 1000 deaths. This compares favorably with previously published studies identifying mortality rates of 0.9 in physically active men aged 15-34 years in Norway [26], but is higher than studies of sudden cardiac death among athletes in Italy (0.28) [21]. When compared to published rates of footballrelated sudden cardiac death, our finding (0.41) is lower [3,27].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the present study, football-related age-specific mortality was found to be 0.41 per 100,000 population and proportional mortality was 0.30 per 1000 deaths. This compares favorably with previously published studies identifying mortality rates of 0.9 in physically active men aged 15-34 years in Norway [26], but is higher than studies of sudden cardiac death among athletes in Italy (0.28) [21]. When compared to published rates of footballrelated sudden cardiac death, our finding (0.41) is lower [3,27].…”
Section: Discussionsupporting
confidence: 78%
“…The incidence of sudden cardiac death in athletes indicates controversial results, largely due to the fact that studies attempt to determine the incidence of sudden cardiac death using different calculations [28]. Football-related sudden cardiac death, though rare, is a problem that requires attention [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations